Cohort study of the effect of surgical repair of symptomatic diastasis recti abdominis on abdominal trunk function and quality of life. Issue 6 (11th September 2019) - Olsson, A.; Kiwanuka, O.; Wilhelmsson, S.; Sandblom, G.; Stackelberg, O.
Abstract : Background: During pregnancy, women are at risk of developing persistent symptomatic diastasis recti abdominis (DRA), which may have a detrimental effect on their physical function and quality of life (QoL). The aim of this prospective cohort study was to determine the effect of surgical repair of DRA on abdominal trunk function, urinary incontinence and QoL in postpartum women with trunk instability symptoms resistant to training. Methods: Postpartum women with diagnosed DRA and training‐resistant symptoms underwent double‐row plication of the linea alba. Abdominal trunk function was evaluated as the primary endpoint using a multimodal examination tool, the Abdominal Trunk Function Protocol. Recurrence was assessed by CT, urinary incontinence was evaluated using the Urogenital Distress Inventory (UDI‐6) and Incontinence Impact Questionnaire (IIQ‐7), and QoL was assessed with the Short Form 36 (SF‐36®) questionnaire. All subjects were examined before and 1 year after surgery. Results: Sixty women were recruited. There was no DRA recurrence at the 1‐year follow‐up. Self‐reported abdominal trunk function had improved in 98 per cent of patients, with a mean score improvement of 79·1 per cent. In the physiological tests monitored by a physiotherapist, 76 per cent performed better and endured exercise tests longer than before surgery. All SF‐36® subscales improved significantly compared with preoperative scores and reached levels similar to, or higher than, the normative Swedish female population. For the UDI‐6 and IIQ‐7, 47 and 37 per cent respectively reported fewer symptoms at follow‐up than before surgery, and 13 and 8 per cent respectively reported more symptoms. Conclusion: In this series of postpartum women presenting with DRA and symptoms of trunk instability resistant to training, surgical reconstruction resulted in a significant improvement in abdominal trunk function, urinary incontinence and QoL. Abstract : Persistent diastasis recti abdominis after pregnancy may cause abdominal trunk dysfunctions. Surgical reconstruction improves abdominal trunk function evaluated with the novel Abdominal Trunk Function Protocol, as well as urinary incontinence and quality of life. Surgical reconstruction when physical training fails Abstract : Antecedentes: Durante el embarazo, las mujeres tienen el riesgo de desarrollar una diástasis rectoabdominal persistente y sintomática ( diastasis rectoabdominis, DRA) que puede tener un efecto perjudicial en su función física y en la calidad de vida ( quality of life, QoL). El objetivo de este estudio de cohortes prospectivo fue determinar el efecto de reparación quirúrgica de la DRA en la función de la musculatura de la pared abdominal, la incontinencia urinaria y la QoL en mujeres con síntomas postparto de inestabilidad de la musculatura abdominal resistentes al entrenamiento. Métodos: Sesenta mujeres diagnosticadas en el postparto de DRA y con síntomas resistentes al entrenamiento se sometieron a una plicatura de doble capa de la línea alba. El objetivo primario fue evaluar la función de la musculatura de la pared abdominal mediante una herramienta de examen multimodal, el protocolo de la función de la pared abdominal ( abdominal trunk function protocol, ATFP). La recidiva se evaluó mediante tomografía computarizada, la incontinencia urinaria utilizando los cuestionarios UDI‐6 y IIQ‐7 y la calidad de vida con el cuestionario SF‐36. Todas las participantes fueron examinadas antes de la cirugía y un año después de la misma Resultados: Tras un año de seguimiento, no hubo recidiva de la DRA. Según informaron las pacientes, la función de la musculatura abdominal había mejorado en el 98, 2% de los casos, con una mejoría en la puntuación media del 79, 1%. En las pruebas fisiológicas controladas por un fisioterapeuta, el 76, 0% presentó mejoría y aumentó la duración en las pruebas de resistencia en comparación con antes de la cirugía. Todas las subescalas del SF‐36 mejoraron significativamente en comparación con las puntuaciones preoperatorias y alcanzaron niveles similares o superiores a los de la población femenina sueca normal. Para el UDI‐6 y el IIQ‐7, el 46, 7% y el 36, 7% respectivamente, manifestaron menos síntomas en el seguimiento que antes de la cirugía, mientras que el 13, 3% y el 8, 3% respectivamente, reportaron más síntomas. Conclusión: En esta serie de mujeres que presentan DRA en el posparto y síntomas de inestabilidad de la musculatura abdominal resistente al entrenamiento, la reconstrucción quirúrgica produjo una mejora significativa en la función de la musculatura abdominal, la incontinencia urinaria y la calidad de vida.